Antral follicle count (AFC) and serum anti-Müllerian hormone (AMH) are the predictors of natural fecundability have similar trends irrespective of fertility status and menstrual characteristics among fertile and infertile women below the age of 40 years - Haroon Latif Khan; Shahzad Bhatti; Samina Suhail; Rohina Gul; Aisha Awais; Humaira Hamayun; Farah Enver; Sana Abbas; Zahira Hassan; Rameen Nisar; Saba Sardar; Warda Asif (BMC, 2019)
Abstract Background Despite being born with a significant number of primordial cells which representing the ancestor cells of the germ-line, women experience a depletion of ovarian reserve and sub-fertility mid-way into their healthy lives. The poor ovarian response is a substantial limiting factor amplified with higher maternal age and associated with a considerably lower likelihood of pregnancy. Methods A present analytical prospective cross-sectional study was conducted to explore whether infertile women below the age of 40 years have low ovarian reserve than fertile women of same age, assessed by Antral follicle count (AFC) and anti-Müllerian hormone (AMH), at tertiary care infertility center: Lahore Institute of Fertility and Endocrinology, Hameed Latif Hospital. The study population including 423 infertile and 388 fertile female patients from June 2013 to November 2016. Patients and controls were aged between 25 and 39 years. Serum levels of FSH, LH, AMH were assessed, and AFC was measured by transvaginal sonography on cycle days 2 or 3. Results A total of 35.6% of infertile women stated a menstrual cycle length shorter than 21 days, while 21% had a regular cycle length between 24 and 38 days, and 43.2%, longer than 38 days. Overall, the two cohorts did not significantly differ on cycle length. The age-specific reduction of the ovarian reserve was similar in both cohorts; serum AMH concentration decreased by 6% (95% Cl: 5-8%) and AFC decline by 4.5% (95% Cl: 5-7%) per year with increased age. Aged patients (36-39 years) had a 5.3% (95% Cl, 1.5; 7.2) higher risk ratio of having an AMH level < 0.7 ng/ml than women of younger age groups (Kruskal-Wallis test, p < 0.01). Conclusion This study indicates that the possible common observation of low respondent in ART might not be a result of over-representation of patients with an early age-specific decline in the ovarian reserve, but rather primarily as a consequence of age-specific depletion in the stock of developing follicles at the time of recruitment and selection.